2005
DOI: 10.1175/jtech1754.1
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Relative Humidity Sensors at the WMO Radiosonde Intercomparison Experiment in Brazil

Abstract: The quality of the vertical distribution measurements of humidity in the atmosphere is very important in meteorology due to the crucial role that water vapor plays in the earth's energy budget. The radiosonde is the humidity measurement device that provides the best vertical resolution. Also, radiosondes are the operational devices that are used to measure the vertical profile of atmospheric water vapor. The World Meteorological Organization (WMO) has carried out several intercomparison experiments at differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 10 publications
2
18
0
Order By: Relevance
“…This result is similar to ones obtained by other works, which reported that the RS80 appears to have a dry bias (Turner et al 2003;Revercomb et al 2003;Sapucci et al 2005). …”
Section: ) Analysis Of the Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…This result is similar to ones obtained by other works, which reported that the RS80 appears to have a dry bias (Turner et al 2003;Revercomb et al 2003;Sapucci et al 2005). …”
Section: ) Analysis Of the Resultssupporting
confidence: 92%
“…Turner et al (2003), using a microwave radiometer, suggested that daytime RS80 is typically 3%-4% drier than nighttime. Sapucci et al (2005), in a WMO radiosonde intercomparison experiment in Brazil, reported drier diurnal behavior to the order of 5.9% (or 2.9 kg m…”
Section: ϫ2mentioning
confidence: 98%
See 1 more Smart Citation
“…However, the network has not been explicitly designed to cater for the taxing requirements of climate monitoring, and it is heavily affected by technological and processing changes that act to mask any small climate signals that may be present in the data (e.g., Elliott and Gaffen 1991;Elliott 1995;Soden and Lanzante 1996;Sapucci et al 2005). Individual station humidity records will contain changes in the measured humidity over time that result from changes in measurement technology (e.g., resistance, capacitive, or skin hygristors), instrument design (e.g., housing of the instruments or inclusion of multiple sensors), instrument response times, and on-site or other data processing (e.g., Wade 1994;Elliott et al 1998).…”
Section: Strategymentioning
confidence: 99%
“…Unlike radiosonde temperature records, whose discontinuities primarily result from sensor-dependent biases, the discontinuities in monthly humidity time series result not only from hygrometer-dependent biases (measurement bias) (Wang et al 2003;Sapucci et al 2005;Wang and Zhang 2008) but also from changes in sampling (sampling bias). For example, as radiosonde hygrometers have been improved over time to have shorter response time and smaller errors under cold conditions, there has been increased sampling-reporting of cold and dry conditions at a given pressure level.…”
Section: Introductionmentioning
confidence: 99%